Significance of using a Superpave Gyratory Compactor to Simulate Field Compaction of Fine Grained Soil - Khaled, Zeyad S.M.; Abed, Alaa H.; Nsayif, Tabarek S. (Al-Nahrain Journal for Engineering Sciences, 2017)
Field compaction equipment used for fine grained soil usually applies a kneading action or vibration that produces shear forces which also reshape soil particles arrangement. A state that might not be completely simulated by laboratory Proctor tests. This study aims at investigating the significance of using the newer modified Texas superpave gyratory compactor (SGC) to simulate field compaction of fine grained soil due to itsability to apply loads in different anglesgenerating shear forces on the compacted soilspecimens. Two types of soil (A-4) and (A-7-6)were compacted using standard Proctor,modified Proctor and (SGC). The results werecompared to dry field densities of the same soilin order to evaluate the most representative test.It was found that maximum dry densities of soiltype (A-4) obtained using (SGC) under (200kPa) and (600 kPa) were lower by (2.07%) andhigher by (1.35%) than the maximum drydensities obtained using standard and modifiedProctor tests respectively. It was also found thatmaximum dry densities of soil type (A-7-6)obtained using (SGC) under (300 kPa) and (600kPa) were lower by (1.02%) and higher by(1.23%) than the maximum dry densitiesobtained using standard and modified Proctortests respectively. The aforementionedconfinement pressure values were applied inorder to achieve dry densities similar to thatobtained by Proctor tests. When comparinglaboratory results to dry filed densities, it wasfound that (SGC) test results were slightly closerto them than Proctor tests results. Nevertheless,the difference between (SGC) and Proctor testsresults seems to be insignificant for these typesof soil compared to the higher effort needed toperform (SGC) tests.